Thermal decomposition of zinc hexacyanometalates in various gas media - D.P. Domonov; S.I. Pechenyuk; R.V. Marchenko (Chemical Thermodynamics and Thermal Analysis)
Prussian blue analogues with formulae Zn3[Co(CN)6]2·10H2O and Zn3[Fe(CN)6]2·4H2O have been synthesized. Their thermal decomposition was studied in oxidizing (air), reducing (hydrogen) and inert (argon) atmospheres in the temperature range from 20 to 1000°C. TG-DSC curves were obtained and solid products of thermolysis were analyzed. It was found that metal-carbon compositions are formed in argon atmosphere, and the sizes of metal particles are 6-26 nm. This study allows us to consider thermolysis of complex compounds as a way to obtain new materials, which may be useful in the field of materials science.